Magnetic Seizure Therapy Compared to Electroconvulsive Therapy for Schizophrenia: A Randomized Controlled Trial - Jiang, Jiangling; Li, Jin; Xu, Yuanhong; Zhang, Bin; Sheng, Jianhua; Liu, Dengtang; Wang, Wenzheng; Yang, Fuzhong; Guo, Xiaoyun; Li, Qingwei; Zhang, Tianhong; Tang, Yingying; et al. (Frontiers in Psychiatry, 2021)
Background: Magnetic seizure therapy (MST) is a potential alternative to electroconvulsive therapy (ECT). However, reports on the use of MST for patients with schizophrenia, particularly in developing countries, which is a main indication for ECT, are limited. Methods: From February 2017 to July 2018, seventy-nine inpatients who met the DSM-5 criteria for schizophrenia were randomized to receive ten sessions of MST (43 inpatients) or ECT (36 inpatients) over the course of 4 weeks. At baseline and 4-week follow-up, the Positive and Negative Syndrome Scale (PANSS) and the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) were used to assess symptom severity and cognitive functions, respectively. Results: Seventy-one patients who completed at least half of the treatment protocol were included in the per-protocol analysis. MST generated a non-significant larger antipsychotic effect in terms of a reduction in PANSS total score (g = 0.17, 95% confidence interval [CI] = −0.30, 0.63) and response rate (relative risk [RR] = 1.41, 95% CI = 0.83 to 2.39). Twenty-four participants failed to complete the cognitive assessment as a result of severe psychotic symptoms. MST showed significant less cognitive impairment over ECT in terms of immediate memory (g = 1.26, 95% CI = 0.63 to 1.89), language function (g =1.14, 95% CI = 0.52 to 1.76), delayed memory (g = 0.75, 95% CI = 0.16 to 1.35), and global cognitive function (g = 1.07, 95% CI = 0.45 to 1.68). The intention-to-treat analysis generated similar results except for the differences in delayed memory became statistically insignificant. Better baseline cognitive performance predicted MST and ECT response. Conclusions: Compared to bitemporal ECT with brief pulses and age-dose method, MST had similar antipsychotic efficacy with fewer cognitive impairments, indicating that MST is a promising alternative to ECT as an add-on treatment for schizophrenia.